Propagación in vitro de Swietenia macrophylla King utilizando ácido Naftalenacético (ANA) y Bencilaminopurina (BAP) - Campos Ruiz, Joseph (2019)
ABSTRACT Mahogany (Swietenia macrophylla King.), is a widely used timber tree species valued for its hardness, strength, beauty and quality. The abundance of mahogany has greatly reduced in much of its natural space because of Intensive exploitation and wood extractions, that's why it's feared for the survival of many populations of the species; as well as for the sustainability of its trade. In vitro culture is an alternative in the production of large volumes of high quality short-term plants. To establish concentrations of ANA and BAP for the in vitro propagation of Swietenia macrophylla King "mahogany was the objective of this research. The methodology included the disinfection of nodal segments, these were immersed in 96% alcohol for three minutes, rinsed three times with sterile distilled water submerged in Ca(ClO)2 and 3% NaClO plus three drops of tween for 10, 15 and 20 minutes for each treatment. Nodal segments of plants that germinated from botanical seeds under in vitro conditions were also used. For the disinfection of botanical seeds in vitro the seed coat had to be removed from the seed and then immersed in 70% alcohol for 30 seconds, rinsed three times with sterile distilled water, then submerged in 0.5% NaClO 10 and 20 minutes for each treatment. The healthy explants were transferred to different culture media such as the MS, WPM and Hydroponic LM mediums for their growth. Subsequently, the explants were exposed to different levels of BAP (0.1, 0.5 1 mg / l) and ANA (0.1 and 0.5 mg / l) for its multiplication. To facilitate rooting, the best shoots of the multiplication phase were placed in culture media with different concentrations of BAP (0.5 and 1 mg / l) and ANA (1 and 2 mg / l). The results show that the nodal segments treated with 3% NaClO during 15 minutes presented a higher percentage of sterile explants (87%). In the growth stage, the culture medium with the best results was the WPM, allowing bud lengths on average of 7.20 mm. The treatment containing the WPM medium plus 1 mg / l BAP allowed bud lengths on average of 8 mm and was the best treatment for the multiplication stage and the rooting phase the best treatment was Treatment two, which contained 1 mg / l of ANA generating roots at 50 days.